Treatment of Hypothyroid Patients With L-Thyroxine (L-T4) Plus Triiodothyronine Sulfate (T3S). A Phase II, Open-Label, Single Center, Parallel Groups Study on Therapeutic Efficacy and Tolerability - Santini, Ferruccio; Ceccarini, Giovanni; Pelosini, Caterina; Giannetti, Monica; Ricco, Ilaria; Querci, Giorgia; Grossi, Enzo; Saponati, Giorgio; Vitti, Paolo (Frontiers in Endocrinology, 2019)
Sodium salt of levothyroxine (L-T4) is the treatment of choice of hypothyroidism. Yet, L-T4 monotherapy produces supoptimal 3,5,3’-triiodothyronine (T3)/T4 ratio in serum, as compared to normal subjects, and a minority of hypothyroid individuals on L-T4 complain for an incomplete wellbeing. Orally administered 3,5,3’-triiodothyronine sulfate (T3S) can be converted to T3 in humans, resulting in steady-state serum T3 concentrations for up to 48 hours. In this study (EudraCT number 2010-018663-42), 36 thyroidectomized hypothyroid patients receiving 100 (group A), 125 (group B) or 150 g (group C) L-T4 were enrolled in a 75 days study in which 25 g L-T4 were replaced by 40 g of T3S. A significant, progressive reduction in mean FT4 values was observed, being the largest in the group A and the smallest in group C, while no relevant variations in FT3 and total T3 serum values were observed in the 3 groups. TSH serum levels increased in all groups, the highest value being observed in group A. Lipid parameters did not show clinically significant changes in all groups. No T3S-related changes in the safety laboratory tests were recorded. No adverse event was judged as related to experimental treatment, and no patient discontinued the treatment. 12 patients judged the L-T4+T3S treatment better than L-T4 alone, while no patient reported a preference for L-T4 over the combined treatment. In conclusion, the results of this study indicate that a combination of L-T4+T3S in hypothyroid subjects may allow mainteinance of normal levels of serum T3, with restoration of a physiological FT4/FT3 ratio and no appearance of adverse events. Further studies are required to verify whether the LT4+T3S chronic combined treatment of hypothyroidism is able to produce additional benefits over L-T4 monotherapy.